Clinical practice guidelines for diagnosis and management of Helicobacter pylori infection in gastroduodenal diseases of the Peruvian Health Social Security (EsSalud) - Otoya-Moreno, Guillermo (2021)
Introduction: This article summarizes the evidence-based recommendations of the clinical practice guide (CPG) for the diagnosis and management of Helicobacter pylori infection in gastroduodenal diseases. Methods: For the provision of these recommendations, a guideline development group (local GDG) was established, including medical specialists and methodologists that formulated seven clinical questions. Systematic searches of systematic reviews and -when it was considered pertinent- primary studies were conducted in PubMed and CENTRAL during December 2017 and July 2019. The evidence to answer each of the posed clinical questions was selected. The quality of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work meetings, the local GDG used the GRADE methodology to review the evidence and formulate the recommendations, points of good clinical practice, and flowcharts. Finally, the CPG was approved with Resolution N° 104-IETSI-ESSALUD-2020. Results: This CPG addressed seven clinical questions, divided into four topics. Based on these questions, 12 recommendations (3 strong and 9 weak), 17 points of good clinical practice, and two flowcharts (one for diagnosis and another for management) were formulated. Conclusion: This article summarizes the methodology and evidence-base PG for for the diagnosis and management of Helicobacter pylori infection in gastroduodenal diseases.